Function of CTLGA9 Amino Acid Residue Leucine-6 in Modulating Cry Toxicity - Alam, Intikhab; Batool, Khadija; Idris, Aisha Lawan; Tan, Weilong; Guan, Xiong; Zhang, Lingling (Frontiers in Immunology, 2022)
Aedes aegypti is a crucial vector for many arboviral diseases that cause millions of deaths worldwide and thus is of major public health concern. Crystal (Cry) proteins, which are toxins produced by Bacillus thuringiensis, are structurally organized into three-domains, of which domain II is the most variable in terms of binding towards various toxin receptors. The binding of Cry11Aa to putative receptor such as aminopeptidase-N (APN) is explicitly inhibited by midgut C-type lectins (CTLs). The similarity between the domain II fold of Cry11Aa toxin and the carbohydrate recognition domain in the CTLs is a possible structural basis for the involvement of Cry domain II in the recognition of carbohydrates on toxin receptors. In this study, a site-directed point mutation was introduced into the A. aegypti CTLGA9 gene on the basis of molecular docking findings, leading to substitution of the Leucine-6 (Leu-6) residue in the protein with alanine. Subsequently, functional monitoring of the mutated protein was carried out. Unlike the amino acid residues of wild-type CTLGA9, none of the residues of mutant (m) CTLGA9 were competed with Cry11Aa for binding to the APN receptor interface. Aditionally, ligand blot analysis showed that both wild-type and mutant CTLGA9 had similar abilities to bind to APN and Cry11Aa. Furthermore, in the competitive ELISA in which labeled mutant CTLGA9 (10 nM) was mixed with increasing concentrations of unlabeled Cry11Aa (0–500 nM), the mutant showed no competition with Cry11Aa for binding to APN. , By contrast, in the positive control sample of labeled wild type CTLGA9 mixed with same concentrations of Cry11Aa competition between the two ligands for binding to the APN was evident. These results suggest that Leucine-6may be the key site involved in the competitive receptor binding between CTLGA9 and Cry11Aa. Moreover, according to the bioassay results, mutant CTLGA9 could in fact enhance the toxicity of Cry11Aa. Our novel findings provide further insights into the mechanism of Cry toxicity as well as a theoretical basis for enhancing the mosquitocidal activity of these toxin through molecular modification strategies.